FAMILY AS A DEVELOPING ENVIRONMENT FOR THE PRESCHOOL CHILD - Marina Lukyanova; Alexey Lukyanov (Вестник Северо-Кавказского федерального университета, 2022)
The article describes the features of the family as educational environment for the preschool child. It's shown the essence and components of environment for child development in the educational process, functions and principles of the family as educational environment, conditions of creating educational environment in the family. Article also concludes essence and components of the subject-developing environment that implements functions that implements functions of preschooler support in the activation of its cognitive interest and orientation in the surrounding world that provides him the full harmonious development.